Currency speculation around the opening of the telegraph between London and Paris in 1851 - Nils Herger (Swiss National Bank, Study Center Gerzensee, 2024)
This paper employs the opening of the first international telegraph between London and Paris on 13 November 1851 as a unique event that enabled a virtually instantaneous information exchange between the largest financial centers. Before this opening, a London currency speculator comparing the short-term return between British pounds and French francs had to form an expectation about the current exchange rate in Paris. With the telegraph, this expectation became suddenly obsolete. Weekly data around 1851 suggest that returns in London and Paris were closely aligned. Apparently, currency speculators held on average quite accurate exchange-rate expectations before the introduction of the telegraph.
Keywords: F31; N13; N23; 330; bills of exchange; currency speculation; exchange rates; interest-parity condition; telegraph